"Bleaching" glycerol in a microfluidic fuel cell to produce high power density at minimal cost. Issue 2 (11th December 2017) - Martins, Cauê A.; Ibrahim, Omar A.; Pei, Pei; Kjeang, Erik
Abstract : Glycerol/bleach flow-through microfluidic fuel cells are presented. Abstract : Glycerol/bleach flow-through microfluidic fuel cells are presented. Carbon paper-modified Pt/C nanoparticles were used as the anode and cathode. Glycerol oxidation in alkaline medium was tested against hypochlorite reduction in alkaline and acidic media. The mixed media system displayed a power density of 315 mW cm −2 and an open circuit voltage of 1.9–2.0 V.